Prioritizing financial and mental wellness - Ismail, Fadillah; Abdul Kadir, Adibah; Salleh, Siti Hasliah (Penerbit Uthm, 2019)
Financial well-being is one of the well-being components other than profession, physical, social and community (Rath & Harter, 2010). The expanding dimension of way of life, questionable way of life propensities, and assortment of responsibilities and vacillation of anxiety can affect towards individual budgetary prosperity as well as among workers for the most part. Representative's budgetary prosperity showed a huge association with worker's efficiency (Zaimah, Masud, Haron, Othman, Awang, & Sarmila, 2013).